2022
DOI: 10.1134/s0965544122100097
|View full text |Cite
|
Sign up to set email alerts
|

Perstraction of Heat-Stable Salts from Aqueous Alkanolamine Solutions

Abstract: Amine absorption processes designed to remove acid gases from gas streams generally face a major challenge of solvent degradation. This degradation leads to the formation of heat-stable salts (HSS), corrosive agents that irreversibly bind free alkanolamine. The present study proposes, for the first time, a method for HSS perstraction using a liquid–liquid membrane contactor that allows HSS to transfer through porous membranes from the solvent into a hydrophobic extractant represented by a methyltrioctylammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In addition to the direct interest in studying the structure of the obtained PSF hollow fibers and their comparison with commercial PVDF fibers, characterization of the membranes may be of further interest. In our previous work [ 39 ], it was shown that the porous structure of the membrane can be changed during contact with an alkanolamine CO 2 solvent and the OH-Aliquat ® 336 solution in n-octanol. Changes in the membrane morphology and porous structure can affect the membrane-supported liquid-liquid extraction process and provide explanations for some of the observed effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the direct interest in studying the structure of the obtained PSF hollow fibers and their comparison with commercial PVDF fibers, characterization of the membranes may be of further interest. In our previous work [ 39 ], it was shown that the porous structure of the membrane can be changed during contact with an alkanolamine CO 2 solvent and the OH-Aliquat ® 336 solution in n-octanol. Changes in the membrane morphology and porous structure can affect the membrane-supported liquid-liquid extraction process and provide explanations for some of the observed effects.…”
Section: Resultsmentioning
confidence: 99%
“…Since the PVDF membrane is completely wetted with MEA solution [ 39 ], the porous structure of the membrane is likely to be filled with the MEA solution with HSS ions, and the mass transfer surface will be close to the extractant solution or within the pores close to the organic phase. At the same time, when using PSF membranes, their porous structure will be more filled with OH-modified Aliquat ® 336 solution in n-octanol.…”
Section: Resultsmentioning
confidence: 99%
“…Kostyanayaa et al. designed a new method of combining liquid‐liquid membranes with organic solvents for HSS removal 156 . The method achieved selective HSS anion extraction by avoiding the direct mixture of liquid phases.…”
Section: Reclamation Procedures Of Alkanolamines and The Removal Of Hsssmentioning
confidence: 99%
“…Kostyanayaa et al designed a new method of combining liquid-liquid membranes with organic solvents for HSS removal. 156 The method achieved selective HSS anion extraction by avoiding the direct mixture of liquid phases. Polypropylene, polysulfone, and polyvinylidene fluoride were the tested membranes, while the extractant contained 1-octanol and aliquat 336.…”
Section: Solvent Extractionmentioning
confidence: 99%
“…The current prominent commercial method for CO 2 capture in the industry is the alkanolamine-based scrubbing process, which mainly utilizes aqueous solutions of alkanolamines to absorb CO 2 chemically [ 4 , 5 ]. However, alkanolamine-based sorption systems have several inherent drawbacks, such as solvent degradations, equipment corrosion, and high absorbent regeneration energy [ 6 , 7 ]. Thus, developing new efficient sorption systems capable of avoiding the above-mentioned drawbacks is one of the main challenges in the field of carbon capture and storage [ 8 ].…”
Section: Introductionmentioning
confidence: 99%